U.S. Health Care Reform - Nedde, Ellen (Washington, D.C. : International Monetary Fund, 1993)
High and rapidly rising health care costs in the United States and growing ranks of uninsured persons have brought health care reform to the top of the U.S. Administration's policy agenda. This paper describes the health care financing system in the United States, highlights what are viewed as its most serious shortcomings, and explores possible reasons for high and rising medical care costs. After brief descriptions of alternative reform proposals, the paper discusses universal coverage under managed competition and its ability to deal with the equity and efficiency problems in the U.S. health care system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet